1993
DOI: 10.1128/jb.175.17.5445-5451.1993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of genetic maps for two Leptospira interrogans serovars provides evidence for two chromosomes and intraspecies heterogeneity

Abstract: Genetic maps were constructed for Leptospira interrogans serovars icterohaemorrhagiae and pomona. Previously we independently constructed physical maps of the genomes for these two serovars. The genomes of both serovars consist of a large replicon (4.4 to 4.6 Mb) and a small replicon (350 kb). Genes were localized on the physical maps by using Southern blot analysis with specific probes. Among the probes used were genes encoding a variety of essential enzymes and genes usually found near bacterial chromosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
98
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 49 publications
4
98
0
3
Order By: Relevance
“…In R. sphaeroides, two rRNA operons are located on the smaller replicon of 900 kb, while one rRNA operon is present on the 3 Mb replicon; both replicons are considered to be chromosomes (Suwanto and Kaplan, 1989). In B. cereus, the chromosome appears to vary in size between 2.4 and 6.3 Mb Leptospira interrogans is another bacterium in which housekeeping genes are present on two replicons: asd is localized on a 350 kb replicon, rather than on the chromosome of 4.4-4.6 Mb (Zuerner et al, 1993). Clearly, complex genomes in bacteria are more common than hitherto anticipated, and the presence of two or more chromosomes, each with housekeeping genes, may not be so rare in bacteria.…”
Section: Flexible Elements Within a Chromosomementioning
confidence: 99%
“…In R. sphaeroides, two rRNA operons are located on the smaller replicon of 900 kb, while one rRNA operon is present on the 3 Mb replicon; both replicons are considered to be chromosomes (Suwanto and Kaplan, 1989). In B. cereus, the chromosome appears to vary in size between 2.4 and 6.3 Mb Leptospira interrogans is another bacterium in which housekeeping genes are present on two replicons: asd is localized on a 350 kb replicon, rather than on the chromosome of 4.4-4.6 Mb (Zuerner et al, 1993). Clearly, complex genomes in bacteria are more common than hitherto anticipated, and the presence of two or more chromosomes, each with housekeeping genes, may not be so rare in bacteria.…”
Section: Flexible Elements Within a Chromosomementioning
confidence: 99%
“…Some bacteria, such as Borrelia burgdorferi and Rhodococcus fascians, have linear chromosomes (4,20,24), whereas Streptomyces lividans and Streptomyces coelicolor have linear chromosomes that may become circular as a result of deletions spanning both telomeres (34,35). Still others, such as Brucella melitensis and Leptospira interrogans, have segmented genomes (40,63). The segmented genome of Agrobacterium tumefaciens has one circular and one linear component (1).…”
mentioning
confidence: 99%
“…Analysis of different strains of Clostriditrm perfringens belonging to different biotypes showed that the overall organization of the chromosome in that bacterium is wellconserved (Canard e t al., 1992). By contrast, the chromosomes of two strains of L. interrogans exhibit several major D N A rearrangements (Zuerner et al, 1993) …”
Section: Physical and Genetic Maps Of The Linear Chromosomementioning
confidence: 98%